2016
DOI: 10.1590/s0102-865020160080000001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of photobiomodulation therapy on Staphylococcus aureus infected surgical wounds in diabetic rats. A microbiological, histopathological, and biomechanical study

Abstract: PURPOSE:To evaluate the effects of photobiomodulation therapy (PBMT) at 685 nm on diabetic wound healing in rats suffering from bacterial infection induced by Staphylococcus aureus (S. aureus). METHODS:Thirty streptozotocin-induced diabetic rats were allocated into two groups: control and PBMT. A 4-cm full-thickness linear-incision was made on the dorsal midline and was contaminated with S. aureus. The wounds in the PBMT group were irradiated daily for 5 consecutive days, starting 3 days after the induction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…PBM also resulted in significantly shorter wound length (on days 14 and 21), and a significant increase in the number of macrophages, new blood vessels, fibroblasts, and collagen deposition. The breaking strength of the scars was also significantly increased in PBM treated rats [67]. This study has shown the potential of utilizing PBM in the treatment of infected diabetic wounds.…”
Section: Photobiomodulation For Diabetic Wound Healingsupporting
confidence: 52%
See 1 more Smart Citation
“…PBM also resulted in significantly shorter wound length (on days 14 and 21), and a significant increase in the number of macrophages, new blood vessels, fibroblasts, and collagen deposition. The breaking strength of the scars was also significantly increased in PBM treated rats [67]. This study has shown the potential of utilizing PBM in the treatment of infected diabetic wounds.…”
Section: Photobiomodulation For Diabetic Wound Healingsupporting
confidence: 52%
“…A study on the effect of PBM on S. aureus infected wounds in diabetic rats was conducted by Ranjbar and colleagues [67]. Streptozotocin-induced male Wistar rats received 4 cm full-thickness linear incisions on the dorsal midline which were contaminated with 5 × 10 7 CFU/mL of S. aureus.…”
Section: Photobiomodulation For Diabetic Wound Healingmentioning
confidence: 99%
“…E. coli ( 35 - 38 ), K. pneumonia ( 39 - 41 ), P. aeruginosa ( 42 - 43 ), Staphylococcus spp . ( 44 - 45 ), Serratia spp. ( 46 ) , and Shigella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The LumiHeal Protocol has been applied over the last 3 months in 8 patients with complicated treatment-resistant infected wounds. The improvement in the wounds is documented by photographic evidence [15][16][17][18][19][20].…”
Section: Lumihealmentioning
confidence: 99%